Characterizing Groundwater Aquifers in Warasia, Ambon City Using Electrical Resistivity Tomography Data and Archie's Law - Samsul Bahri; Zulfiah; Muh. Riswan Anas Sukri; Yohanis Toni Batlolona; Wildan Nur Hamzah (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
Identifying aquifer characteristics is vital for groundwater management, especially in volcanic terrains. This study employs Electrical Resistivity Tomography (ERT) combined with Archie's Law to delineate subsurface lithology and estimate aquifer porosity in Warasia, Ambon City. Field data were collected using a resistivity meter with two ERT profiles extending 120 meters each. The resistivity data were processed and modeled using RES2DINV, while water samples from wells were analyzed for physical parameters, including pH, conductivity, and total dissolved solids (TDS). The results reveal aquifers at depths of 3–5 meters, primarily hosted in volcanic tuff with resistivity values of 4.22–72.7 Ωm, indicating moderate to fair porosity (7.20%–14.01%). In contrast, lava formations exhibit significantly lower porosity (0.82%–1.02%) due to their solid structure. Archie's Law was instrumental in correlating resistivity with porosity, considering local lithological variability. The findings underscore the effectiveness of integrating ERT and Archie's Law for groundwater exploration in complex geological settings.